Oligomerization of simian virus 40 large T antigen is not necessarily repressed by temperature-sensitive A gene lesions. - Montenarh, M (1984)
Simian virus 40 large T antigen is a multifunctional protein which exists in different molecular weight forms. According to several reports, T antigen encoded by temperature-sensitive simian virus 40 A locus mutants (tsA) is unable to oligomerize into high-molecular-weight species. To try to correlate structural and functional properties, we selected tsA58 and tsA1499, both of which are heat sensitive for lytic growth, but only tsA58 is heat sensitive for transformation. Here we report that at permissive and nonpermissive temperatures, T antigen from tsA1499-infected monkey cells retained the ability to oligomerize, whereas reported previously, tsA58 T antigen failed to oligomerize at the nonpermissive temperature. Furthermore, we studied the formation of complexes between T antigen and the cellular p53 protein (T-p53) late in infection. Corresponding to its heat-stable oligomerization properties, T antigen encoded by tsA1499 formed T-p53 complexes regardless of temperature. In contrast, tsA58 encoded T-p53 complexes, preformed at the permissive temperature, remained heat stable after shifting up to the nonpermissive temperature; but at this temperature no new T-p53 complexes arose. The mutants did not replicate viral DNA at the nonpermissive temperature, suggesting that neither the oligomerization of T antigen nor the formation of T-p53 complexes seems to be sufficient for viral DNA replication or for the expression of late viral proteins.